Resin composition, pellet, and molded article

JP2025034491APending Publication Date: 2025-03-13GLOBAL POLYACETAL CO LTD
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
JP2023140889
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Filing Date
2023-08-31
Publication Date
2025-03-13

AI Technical Summary

Benefits of technology

【0006】 本発明により、耐トラッキング性および難燃性に優れた成形品を提供可能な樹脂組成物、ならびに、ペレット、および、成形品を提供可能になった。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2025034491000001
    Figure 2025034491000001
  • Figure 2025034491000002
    Figure 2025034491000002
  • Figure 2025034491000003
    Figure 2025034491000003
Patent Text Reader

Abstract

To provide a resin composition that can yield a molded article with excellent tracking resistance and flame retardancy, as well as a pellet and a molded article.SOLUTION: A resin composition comprises, based on (A) 100 pts.mass of a polyamide resin, (B) 80 to 230 pts.mass of glass fibers with a cross-sectional area of 130 μm2 or more, (C) 10 to 50 pts.mass of at least one phosphorus-based flame retardant selected from phosphinates and diphosphinates; and (D) 0.2 to 20 pts.mass of a white colorant with a Mohs hardness of 1.0 to 4.5.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin composition, a pellet, and a molded article, and in particular to a resin composition containing a polyamide resin as a main component. [Background technology]

[0002] Polyamide resins are used in a variety of fields because of their excellent performance. In particular, when used in fields that require mechanical strength, reinforcing fibers are blended into the resin. In addition, when used in fields that require flame retardancy, flame retardants are blended into the resin (Patent Document 1, Patent Document 2). [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2008-163317 A [Patent Document 2] JP 2020-172579 A Summary of the Invention [Problem to be solved by the invention]

[0004] As described above, polyamide resin compositions with excellent flame retardancy have been studied. Such flame retardant polyamide resin compositions may also contain a white colorant from the viewpoint of design and shielding properties. Glass fibers may also be added to the composition to strengthen the molded product. Furthermore, in recent years, applications requiring tracking resistance have been increasing. Under these circumstances, there is a demand for a polyamide resin composition containing a white colorant and glass fibers that can achieve both flame retardancy and tracking resistance. The present invention has an object to solve the above problems, and to provide a resin composition capable of providing a molded article having excellent tracking resistance and flame retardancy, as well as pellets and a molded article. [Means for solving the problem]

[0005] As a result of investigations conducted under the above-mentioned conditions, it was found that the above-mentioned problems could be solved by using a large diameter glass fiber and a white colorant having a low Mohs hardness in addition to a specified phosphorus-based flame retardant. Specifically, the above problems were solved by the following means. <1> (A) per 100 parts by mass of polyamide resin (B) 130 μm 2 80 to 230 parts by mass of glass fiber having a cross-sectional area of ​​the above (C) 10 to 50 parts by mass of at least one phosphorus-based flame retardant selected from phosphinates and diphosphinates; (D) A resin composition comprising 0.2 to 20 parts by mass of a white colorant having a Mohs hardness of 1.0 to 4.5. <2> The (A) polyamide resin is a semi-aromatic polyamide resin and contains a structural unit having a linear aliphatic chain having 4 to 7 carbon atoms. <1> The resin composition according to claim 1. <3> The (B) glass fiber has a noncircular cross section. <1> or <2> The resin composition according to claim 1. <4> The (B) glass fiber has an aspect ratio, which is a ratio of the long side to the short side of a cross section, of 2 to 7. <1> ~ <3> 10. The resin composition according to claim 9 . <5> The Mohs hardness of the (B) glass fiber is higher than the Mohs hardness of the (D) white colorant. <1> ~ <4> 10. The resin composition according to claim 9 . <6> The (D) white colorant contains zinc sulfide. <1> ~ <5> 10. The resin composition according to claim 9 . <7> The (A) polyamide resin contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 70 mol % or more of the diamine-derived structural unit is derived from xylylenediamine. <1> ~ <6> 10. The resin composition according to claim 9 . <8> The resin composition is molded into a plate having a thickness of 3 mm or more, and the plate has a tracking voltage of 800 V or more as measured according to IEC 60112. <1> ~ <7> 10. The resin composition according to claim 9 . <9> For protective cases for batteries, for protective cases for connectors, or for protective cases for circuit relays, <1> ~ <8> 10. The resin composition according to claim 9 . <10> The (A) polyamide resin is a semi-aromatic polyamide resin and contains a structural unit having a linear aliphatic chain having 4 to 7 carbon atoms, The (B) glass fiber has an aspect ratio, which is a ratio of the long side to the short side of a cross section, of 2 to 7; The Mohs hardness of the (B) glass fiber is higher than the Mohs hardness of the (D) white colorant, The (D) white colorant contains zinc sulfide, the (A) polyamide resin contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 70 mol % or more of the diamine-derived structural unit is derived from xylylenediamine; The resin composition is molded into a plate having a thickness of 3 mm or more, and the plate has a tracking voltage of 800 V or more as measured according to IEC 60112. <1> ~ <9> 10. The resin composition according to claim 9 . <11> <1> ~ <10> 2. A pellet of the resin composition according to claim 1. <12> <1> ~ <10> 2. A molded article molded from the resin composition according to claim 1. <13> <11> A molded article molded from the pellets according to claim 1. Effect of the Invention

[0006] According to the present invention, it is possible to provide a resin composition capable of providing a molded article having excellent tracking resistance and flame retardancy, as well as pellets and a molded article. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0007] Hereinafter, an embodiment of the present invention (hereinafter, simply referred to as "the present embodiment") will be described in detail. Note that the present embodiment is an example for explaining the present invention, and the present invention is not limited to the present embodiment. In this specification, the use of "to" means that the numerical values ​​before and after it are included as the lower limit and upper limit. In this specification, various physical properties and characteristic values ​​are those at 23° C. unless otherwise specified.

[0008] In this specification, unless otherwise specified, the number average molecular weight is a polystyrene equivalent value measured by GPC (gel permeation chromatography). Specifically, it can be measured according to the description in paragraph 0047 of JP2018-165298A, the contents of which are incorporated herein by reference.

[0009] In this specification, the melting point (Tm) is a value measured according to differential scanning calorimetry (DSC) in accordance with ISO11357, unless otherwise specified. A differential scanning calorimeter is used, and the resin is placed in the measurement pan of the differential scanning calorimeter, heated to a temperature above the melting point at a heating rate of 10°C / min under a nitrogen atmosphere, and then rapidly cooled before measurement. The measurement conditions are a heating rate of 10°C / min, held at 280°C for 5 minutes, and then cooled down to 100°C at a cooling rate of -5°C / min to determine the melting point (Tm). As the differential scanning calorimeter, a "DSC-60" manufactured by SHIMADZU CORPORATION is used. If the measurement methods, etc. described in the standards shown in this specification vary from year to year, they will be based on the standards as of January 1, 2023, unless otherwise stated.

[0010] The resin composition of the present embodiment is a mixture of (A) 100 parts by mass of polyamide resin and (B) 130 μm 2 The composition is characterized by comprising: (A) 80 to 230 parts by mass of glass fibers having the above cross-sectional area; (B) 10 to 50 parts by mass of at least one phosphorus-based flame retardant selected from phosphinates and diphosphinates; and (C) 0.2 to 20 parts by mass of a white colorant having a Mohs hardness of 1.0 to 4.5. By adopting such a constitution, a resin composition capable of providing a molded article having excellent tracking resistance and flame retardancy can be obtained.Furthermore, a resin composition capable of providing a molded article having excellent mechanical strength can be obtained.Furthermore, a resin composition capable of providing a molded article having high whiteness can be obtained.

[0011] In this embodiment, the glass fiber is (B) 130 μm 2 Glass fibers having a cross-sectional area of ​​100 mm or more (hereinafter, sometimes referred to as "large diameter glass fibers") are used. When large diameter glass fibers are used, they are less likely to break during melt-kneading or injection molding of the resin composition. As a result, the remaining fiber length of the glass fibers in the obtained molded product tends to be longer. And, the long remaining fiber length of the glass fibers can improve the tracking resistance. That is, the tracking resistance is caused by the voltage that is conducted in the carbonized portion of the polyamide resin. Therefore, it is presumed that if the fiber length of the remaining glass fibers is longer, the polyamide resin can be made less conductive, improving the tracking resistance. On the other hand, in molded products, a white colorant may be blended to increase the whiteness and to improve the design. However, if the Mohs hardness of the white colorant is high, it promotes the breakage of the glass fiber during melt-kneading or injection molding of the resin composition. Therefore, in this embodiment, by using a white colorant (D) having a Mohs hardness of 1.0 to 4.5 as the white colorant, the breakage of the glass fiber can be effectively suppressed. In addition, in the resin composition of this embodiment, the large diameter glass fibers are present in the molded article in a state in which they are not easily broken, so that a resin composition having excellent mechanical strength can be obtained.

[0012] <(A) Polyamide resin> The resin composition of the present embodiment contains (A) a polyamide resin. The type of polyamide resin used in the present embodiment is not particularly limited, and may be an aliphatic polyamide resin or a semi-aromatic polyamide resin. However, a semi-aromatic polyamide resin is preferable, and a semi-aromatic polyamide resin containing a structural unit having a linear aliphatic chain having 4 to 7 carbon atoms is more preferable. By using a semi-aromatic polyamide resin, tracking resistance tends to be further improved. Also, by using a semi-aromatic polyamide resin containing a structural unit having a linear aliphatic chain having 4 to 7 carbon atoms, self-extinguishing performance tends to be further improved when combined with a flame retardant.

[0013] Examples of aliphatic polyamide resins include polyamide 4, polyamide 46, polyamide 6, polyamide 66, polyamide 666, polyamide 610, polyamide 11, polyamide 12, and the like. As described above, the polyamide resin used in the present embodiment preferably contains a semi-aromatic polyamide resin. For example, it is more preferable that 90 mass % or more of the polyamide resin contained in the resin composition of the present embodiment is a semi-aromatic polyamide resin. Here, the semi-aromatic polyamide resin refers to a polyamide resin that is composed of a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 20 to 80 mol % (preferably 30 to 80 mol %, more preferably 40 to 70 mol %) of the total structural units of the diamine-derived structural unit and the dicarboxylic acid-derived structural unit contains an aromatic ring. In addition, examples of structural units having a linear aliphatic chain having 4 to 7 carbon atoms that are preferably contained in the semi-aromatic polyamide resin include structural units derived from aliphatic diamines having 4 to 7 carbon atoms, structural units derived from aliphatic dicarboxylic acids having 6 to 9 carbon atoms, and structural units derived from lactams having 5 to 8 carbon atoms, and structural units derived from aliphatic diamines having 4 to 7 carbon atoms and / or structural units derived from aliphatic dicarboxylic acids having 6 to 9 carbon atoms are preferred. Examples of the aliphatic diamine having 4 to 7 carbon atoms include tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, and heptamethylenediamine. Examples of the aliphatic dicarboxylic acid having 6 to 9 carbon atoms include adipic acid, pimelic acid, and suberic acid. Examples of lactams having 5 to 8 carbon atoms include δ-lactam and ε-lactam.

[0014] By using such a semi-aromatic polyamide resin, the mechanical strength of the obtained molded product can be increased. Examples of semi-aromatic polyamide resins include terephthalic acid-based polyamide resins (polyamide 6T, polyamide 9T, polyamide 10T) and xylylenediamine-based polyamide resins described below.

[0015] In this embodiment, a polyamide resin containing diamine-derived structural units and dicarboxylic acid-derived structural units, in which 70 mol % or more of the diamine-derived structural units are derived from xylylenediamine (hereinafter sometimes referred to as a "xylylenediamine-based polyamide resin") is preferred.

[0016] The diamine-derived constituent units of the xylylenediamine-based polyamide resin are more preferably 75 mol% or more, even more preferably 80 mol% or more, even more preferably 90 mol% or more, still more preferably 95 mol% or more, and particularly preferably 99 mol% or more, derived from xylylenediamine (preferably paraxylylenediamine and / or metaxylylenediamine).

[0017] The xylylenediamine is preferably paraxylylenediamine and / or metaxylylenediamine. The xylylenediamine preferably contains 0 to 100 mol% metaxylylenediamine and 100 to 0 mol% paraxylylenediamine (however, the sum of metaxylylenediamine and paraxylylenediamine does not exceed 100 mol%), more preferably contains 10 to 100 mol% metaxylylenediamine and 90 to 0 mol% paraxylylenediamine, even more preferably contains 20 to 10 mol% metaxylylenediamine and 80 to 10 mol% paraxylylenediamine, still more preferably contains 40 to 100 mol% metaxylylenediamine and 60 to 0 mol% paraxylylenediamine, even more preferably contains 60 to 100 mol% metaxylylenediamine and 40 to 0 mol% paraxylylenediamine, and even more preferably contains 60 to 90 mol% metaxylylenediamine and 40 to 10 mol% paraxylylenediamine. In the xylylenediamine-based polyamide resin, the total of the constitutional units derived from paraxylylenediamine and the constitutional units derived from metaxylylenediamine is preferably 80 mol% or more, more preferably 85 mol% or more, even more preferably 90 mol% or more, still more preferably 95 mol% or more, even more preferably 98 mol% or more, and even more preferably 99 mol% or more of the constitutional units derived from diamine. The upper limit of the total of the constitutional units derived from paraxylylenediamine and the constitutional units derived from metaxylylenediamine is 100 mol%. By making the proportion of metaxylylenediamine 10 mol% or more, the flame retardancy of the obtained molded article tends to be further improved.

[0018] Diamines other than metaxylylenediamine and paraxylylenediamine that can be used as the raw diamine component of the xylylenediamine-based polyamide resin include aliphatic diamines such as tetramethylenediamine, pentamethylenediamine, 2-methylpentanediamine, hexamethylenediamine, heptamethylenediamine, octamethylenediamine, nonamethylenediamine, decamethylenediamine, dodecamethylenediamine, 2,2,4-trimethylhexamethylenediamine, and 2,4,4-trimethylhexamethylenediamine, 1,3-bis( Examples of the diamines include alicyclic diamines such as bis(aminomethyl)cyclohexane, 1,4-bis(aminomethyl)cyclohexane, 1,3-diaminocyclohexane, 1,4-diaminocyclohexane, bis(4-aminocyclohexyl)methane, 2,2-bis(4-aminocyclohexyl)propane, bis(aminomethyl)decalin, and bis(aminomethyl)tricyclodecane; and diamines having an aromatic ring such as bis(4-aminophenyl)ether, paraphenylenediamine, and bis(aminomethyl)naphthalene. These can be used alone or in combination of two or more.

[0019] On the other hand, the dicarboxylic acid-derived structural units of the xylylenediamine-based polyamide resin are preferably derived from an aliphatic dicarboxylic acid having 4 to 20 carbon atoms (preferably adipic acid) for 70 mol % or more, more preferably 75 mol % or more, even more preferably 80 mol % or more, still more preferably 90 mol % or more, even more preferably 95 mol % or more, and particularly preferably 99 mol % or more.

[0020] Examples of α,ω-linear aliphatic dicarboxylic acids having 4 to 20 carbon atoms that are suitable for use as the raw dicarboxylic acid component of the xylylenediamine-based polyamide resin include aliphatic dicarboxylic acids such as succinic acid, glutaric acid, adipic acid, azelaic acid, sebacic acid, undecanedioic acid, and 1,12-dodecanedioic acid. One or a mixture of two or more types can be used. Among these, at least one of adipic acid, sebacic acid, and 1,12-dodecanedioic acid is preferred, as the melting point of the polyamide resin falls within a range suitable for molding. Adipic acid and / or sebacic acid is more preferred, and adipic acid is even more preferred.

[0021] Examples of dicarboxylic acid components other than those mentioned above include phthalic acid compounds such as isophthalic acid, terephthalic acid, and orthophthalic acid, and isomers of naphthalenedicarboxylic acids such as 1,2-naphthalenedicarboxylic acid, 1,3-naphthalenedicarboxylic acid, 1,4-naphthalenedicarboxylic acid, 1,5-naphthalenedicarboxylic acid, 1,6-naphthalenedicarboxylic acid, 1,7-naphthalenedicarboxylic acid, 1,8-naphthalenedicarboxylic acid, 2,3-naphthalenedicarboxylic acid, 2,6-naphthalenedicarboxylic acid, and 2,7-naphthalenedicarboxylic acid. These can be used alone or in combination of two or more kinds.

[0022] In addition, the xylylenediamine-based polyamide resin is mainly composed of diamine-derived structural units and dicarboxylic acid-derived structural units, but does not completely exclude other structural units, and may contain lactams such as ε-caprolactam and laurolactam, and aliphatic aminocarboxylic acid-derived structural units such as aminocaproic acid and aminoundecanoic acid. Here, the main component means that the total number of diamine-derived structural units and dicarboxylic acid-derived structural units is the largest among all structural units among the structural units constituting the xylylenediamine-based polyamide resin. In this embodiment, the total of diamine-derived structural units and dicarboxylic acid-derived structural units in the xylylenediamine-based polyamide resin preferably accounts for 90% by mass or more of all structural units, more preferably accounts for 95% by mass or more, even more preferably accounts for 97% by mass or more, and even more preferably accounts for 99% by mass or more.

[0023] It is also preferable to use a polyamide resin produced using a biomass raw material (biomass polyamide resin) as the xylylenediamine-based polyamide resin. By using a biomass polyamide resin, it is possible to reduce the environmental load. For xylylenediamine-based polyamide resins, bio-adipic acid can be used as a biomass raw material. Mass balance certified (ISCC PLUS) adipic acid can also be used. Mass balance certification means that the amount of renewable raw materials and bio-raw materials used at each factory or production facility and the amount of products produced or shipped are quantified and guaranteed along with their quality.

[0024] The melting point of the polyamide resin is preferably 150°C or higher, more preferably 180°C or higher, and even more preferably 200°C or higher, and is preferably 350°C or lower, more preferably 330°C or lower, and even more preferably 300°C.

[0025] The lower limit of the number average molecular weight (Mn) of the polyamide resin is preferably 6,000 or more, more preferably 8,000 or more, and even more preferably 10,000 or more, and is preferably 100,000 or less, and more preferably 50,000 or less. Within such ranges, the heat resistance, elastic modulus, dimensional stability, and moldability are improved.

[0026] The content of the polyamide resin in the resin composition of the present embodiment is preferably 25% by mass or more, more preferably 30% by mass or more, and even more preferably 32% by mass or more, based on 100% by mass of the resin composition. By making it equal to or more than the lower limit, the blending rate of the glass fiber can be suppressed to a certain extent, and the flow balance of the resin composition tends to be easily adjusted. In addition, the content of the polyamide resin in the resin composition of the present embodiment is 50% by mass or less, preferably 45% by mass or less, more preferably 40% by mass or less, and even more preferably 38% by mass or less, based on the resin composition. By making it equal to or less than the upper limit, the blending rate of the glass fiber increases, and high physical properties in terms of rigidity and strength tend to be easily obtained. The resin composition of the present embodiment may contain only one type of polyamide resin, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0027] <(B) Large diameter glass fiber> The resin composition of this embodiment is (B) 130 μm 2 Such glass fibers are less likely to break during melt kneading or injection molding, and can maintain a long glass fiber length in the resulting molded product. The cross-sectional area of ​​the (B) large diameter glass fiber is 130 μm 2 Above 135μm 2 It is preferable that the thickness is 140 μm or more. 2 More preferably, it is 150 μm or more. 2 More preferably, it is 180 μm or more. 2 More preferably, it is 190 μm or more. 2More preferably, it is 300 μm or more. 2 Preferably, it is less than 280 μm. 2 More preferably, it is 250 μm or less. 2 More preferably, it is 220 μm or less. 2 More preferably, it is 200 μm or less. 2 It is even more preferable that the thickness is equal to or less than the lower limit. By making the thickness equal to or more than the lower limit, breakage of the glass fiber during thermal processing tends to be suppressed. Also, by making the thickness equal to or less than the upper limit, the adhesion area with the resin tends to be appropriately secured, and good mechanical properties tend to be exhibited. When the resin composition of the present embodiment contains two or more types of (B) large diameter glass fibers, the cross-sectional area of ​​the (B) large diameter glass fibers is preferably such that the sum (weighted average value) of the cross-sectional area of ​​each large diameter glass fiber multiplied by the mass fraction of each large diameter glass fiber falls within the above range.

[0028] (B) The cross-sectional area of ​​the large diameter glass fiber is measured according to the following method. Before kneading, chopped glass fibers were bundled and embedded in epoxy cured resin. The cross section was polished with a polishing machine and then polished with a #1200 file. The cross-sectional area of ​​the glass fibers exposed on the polished surface was observed and photographed with a scanning electron microscope (SEM). Analysis and measurement were performed on more than 1,000 fibers, and the number average value was used. The obtained images were analyzed using Mitani Shoji's WinRoof.

[0029] The cross section of the glass fiber may be circular or noncircular. In the present embodiment, the cross section is preferably noncircular. By using the large diameter glass fiber with a noncircular cross section, the mechanical strength and tracking resistance of the molded product obtained tend to be improved. Examples of the flat shape of the reinforcing fiber as a non-circular cross section include a cocoon shape with a constricted central portion in the longitudinal direction as shown in (A) of FIG. 1 of JP-A-62-268612, an oval shape with a portion that is approximately parallel to the center of gravity of the cross section as shown in (B), and an ellipse shape as shown in (C). When the flat shape is a cocoon shape, the major axis (d1) in the present invention corresponds to a in FIG. 1 (A) of JP-A-62-268612, and the minor axis (d2) corresponds to b. When the flat shape is an oval shape, the major axis (d1) corresponds to a in FIG. 1 (B) of JP-A-62-268612, and the minor axis (d2) corresponds to b. When the flat shape is an ellipse shape, the major axis (d1) corresponds to a in FIG. 1 (B) of JP-A-62-268612, and the minor axis (d2) corresponds to b. When the flat shape is an ellipse shape, the major axis (d1) corresponds to a in FIG. 1 (C) of Patent Document 2, and the minor axis (d2) corresponds to b. In this embodiment, the cross section of the (B) large diameter glass fiber is preferably oval or elliptical.

[0030] The flattening ratio, which is the ratio of the long side to the short side of the cross section of the (B) large diameter glass fiber, is preferably 2-7, more preferably 3-6, and further preferably 3-5.

[0031] The (B) large diameter glass fiber preferably has a Mohs hardness higher than that of the (D) white colorant. By using glass fibers with a high Mohs hardness, the glass fibers can be made less likely to break. The Mohs hardness of the (B) large diameter glass fiber is preferably more than 4.5, more preferably 4.7 or more, even more preferably 5.0 or more, and even more preferably 5.5 or more, and practically 8.0 or less. In this embodiment, the difference in Mohs hardness between the (B) large diameter glass fiber and the (D) white colorant is preferably 1.0 or more, more preferably 1.5 or more, and is preferably 5.0 or less.

[0032] When the resin composition of the present embodiment contains two or more types of (B) large diameter glass fibers, the Mohs hardness of the (B) large diameter glass fibers is preferably such that the sum (weighted average value) of the values ​​obtained by multiplying the Mohs hardness of each large diameter glass fiber by the mass fraction of each large diameter glass fiber falls within the above range.

[0033] The content of the (B) thick glass fiber in the resin composition of this embodiment is 80 parts by mass or more, preferably 90 parts by mass or more, more preferably 100 parts by mass or more, more preferably 110 parts by mass or more, even more preferably 120 parts by mass or more, even more preferably 130 parts by mass or more, and may be 138 parts by mass or more depending on the application, etc., and may be 230 parts by mass or less, preferably 215 parts by mass or less, more preferably 195 parts by mass or less, even more preferably 185 parts by mass or less, even more preferably 160 parts by mass or less, even more preferably 155 parts by mass or less, and may be 145 parts by mass or less depending on the application, etc. By making it equal to or more than the lower limit, the mechanical strength and tracking resistance tend to be further improved. Also, by making it equal to or less than the upper limit, the flowability during injection molding and the appearance finish of the molded product tend to be further improved.

[0034] The content of the (B) large diameter glass fiber in the resin composition of this embodiment is preferably 45 mass% or more, and is preferably 70 mass% or less, more preferably 65 mass% or less, even more preferably 60 mass% or less, and even more preferably 55 mass% or less. The resin composition of the present embodiment may contain only one type of (B) large diameter glass fiber, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0035] <(C) Phosphorus-based flame retardants> The resin composition of the present embodiment contains at least one phosphorus-based flame retardant selected from phosphinates and diphosphinates, which allows a molded article with excellent flame retardancy to be obtained.

[0036] In the present embodiment, it is further preferable that the (C) phosphorus-based flame retardant contains at least one of the compound represented by formula (I) and the compound represented by formula (II). [ka] (In formula (I), R 1 and R 2 each independently represents a linear or branched alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms; M represents a calcium ion, an aluminum ion, a magnesium ion, or a zinc ion; and m is a natural number representing the valence of M. [ka] (In formula (II), R 4 and R 5 R each independently represents a linear or branched alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms. 3 represents a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 7 to 10 carbon atoms, or an arylalkylene group having 7 to 10 carbon atoms. M represents a calcium ion, an aluminum ion, a magnesium ion, or a zinc ion. n is a natural number representing the valence of M. n, a, and b are natural numbers that satisfy the relational formula 2×b=n×a.)

[0037] In formula (I), R 1 and R 2 each independently represents a linear or branched alkyl group having 1 to 6 carbon atoms, or an aryl group having 6 to 10 carbon atoms, and is preferably a methyl group, an ethyl group, a propyl group, or a phenyl group. M represents a calcium ion, an aluminum ion, a magnesium ion, or a zinc ion. m is a natural number representing the valence of M, and is preferably 2 or 3.

[0038] In formula (II), R 4 and R 5R each independently represents a linear or branched alkyl group having 1 to 6 carbon atoms or an aryl group having 6 to 10 carbon atoms, and is preferably a methyl group, an ethyl group, a propyl group, or a phenyl group. 3 represents a linear or branched alkylene group having 1 to 10 carbon atoms, an arylene group having 6 to 10 carbon atoms, an alkylarylene group having 7 to 10 carbon atoms, or an arylalkylene group having 7 to 10 carbon atoms, and is preferably a methylene group, an ethylene group, a propylene group, or a phenylene group. M represents a calcium ion, an aluminum ion, a magnesium ion, or a zinc ion. n is a natural number representing the valence of M. n, a, and b are natural numbers that satisfy the relational formula 2×b=n×a. n is preferably 2 or 3. b is preferably 1, 2, or 3, and more preferably 1 or 3. a is preferably 1 or 2.

[0039] Specific examples of the phosphinate or diphosphinate include those produced in an aqueous medium using phosphinic acid and a metal carbonate, metal hydroxide, or metal oxide. Although the phosphinate or diphosphinate is basically a monomeric compound, depending on the reaction conditions and the environment, it may become a polymeric phosphinate with a condensation degree of 1 to 3.

[0040] Examples of phosphinic acids or diphosphinic acids include dimethylphosphinic acid, ethylmethylphosphinic acid, diethylphosphinic acid, methyl-n-propylphosphinic acid, methanedi(methylphosphinic acid), benzene-1,4-di(methylphosphinic acid), methylphenylphosphinic acid, and diphenylphosphinic acid.

[0041] Examples of the phosphinate include calcium dimethylphosphinate, magnesium dimethylphosphinate, aluminum dimethylphosphinate, zinc dimethylphosphinate, calcium ethylmethylphosphinate, magnesium ethylmethylphosphinate, aluminum ethylmethylphosphinate, zinc ethylmethylphosphinate, calcium diethylphosphinate, magnesium diethylphosphinate, aluminum diethylphosphinate, zinc diethylphosphinate, calcium methyl-n-propylphosphinate, magnesium methyl-n-propylphosphinate, aluminum methyl-n-propylphosphinate, zinc methyl-n-propylphosphinate, calcium methylphenylphosphinate, magnesium methylphenylphosphinate, aluminum methylphenylphosphinate, zinc methylphenylphosphinate, calcium diphenylphosphinate, magnesium diphenylphosphinate, aluminum diphenylphosphinate, and zinc diphenylphosphinate.

[0042] Examples of diphosphinates include calcium methane di(methylphosphinate), magnesium methane di(methylphosphinate), aluminum methane di(methylphosphinate), zinc methane di(methylphosphinate), calcium benzene-1,4-di(methylphosphinate), magnesium benzene-1,4-di(methylphosphinate), aluminum benzene-1,4-di(methylphosphinate), and zinc benzene-1,4-di(methylphosphinate).

[0043] Among these phosphinates or diphosphinates, aluminum aluminum phosphinates such as aluminum ethylmethylphosphinate and aluminum diethylphosphinate, and zinc phosphinates such as zinc diethylphosphinate are preferred, and aluminum aluminum phosphinate is more preferred, from the viewpoints of flame retardancy and electrical properties. Specific examples of commercial products of phosphinates or diphosphinates include EXOLIT OP 1230 and OP 1400 (both trade names) manufactured by Clariant.

[0044] The content of the phosphorus-based flame retardant (C) in the resin composition of this embodiment is 10 parts by mass or more, preferably 15 parts by mass or more, more preferably 18 parts by mass or more, even more preferably 20 parts by mass or more, and even more preferably 25 parts by mass or more, and 50 parts by mass or less, preferably 45 parts by mass or less, more preferably 40 parts by mass or less, even more preferably 35 parts by mass or less, even more preferably 32 parts by mass or less, and even more preferably 30 parts by mass or less, relative to 100 parts by mass of the polyamide resin (A). By making it equal to or more than the lower limit, the self-extinguishing property during combustion tends to be improved. In addition, by making it equal to or less than the upper limit, the decrease in mechanical strength and the gas and mold contamination during injection molding tend to be suppressed. The resin composition of the present embodiment may contain only one type of (C) phosphorus-based flame retardant, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0045] <(D) White colorant with low Mohs hardness> The resin composition of the present embodiment contains (D) a white colorant having a Mohs hardness of 1.0 to 4.5. By containing such a white colorant having a low Mohs hardness, a white color can be imparted to the obtained molded article, and the breakage of (B) the large diameter glass fiber can be effectively suppressed, resulting in a molded article having excellent tracking resistance.

[0046] The Mohs hardness is a value measured by rubbing a standard mineral with a sample material and classifying the hardness based on the presence or absence of scratches. The higher the Mohs hardness, the harder the material is. The Mohs hardness of the white colorant (D) used in this embodiment is 4.5 or less, preferably 4.0 or less, more preferably 3.5 or less, even more preferably 3.2 or less, and preferably 1.0 or more, more preferably 1.5 or more, even more preferably 2.0 or more, even more preferably 2.5 or more, and even more preferably 2.8 or more. By making it equal to or less than the upper limit, breakage of the glass fiber tends to be suppressed. Also, by making it equal to or more than the lower limit, production stability during blending and kneading tends to be further improved. When the resin composition of the present embodiment contains two or more types of (D) white colorant, the Mohs hardness is preferably such that the weighted average value of the Mohs hardness of each white colorant falls within the above range.

[0047] (D) The white colorant is a colorant that appears white or nearly white to the human eye, and may be a pigment or a dye, although a pigment is preferred. (D) Examples of white colorants having a Mohs hardness of 1.0 to 4.5 include zinc sulfide, lithopone, and zinc oxide, with zinc sulfide being preferred.

[0048] The average primary particle diameter of the (D) white colorant (sometimes simply referred to as the average particle diameter in this specification) is preferably 1 μm or less, more preferably 0.5 μm or less, and even more preferably 0.3 μm or less, and is preferably 0.001 μm or more, more preferably 0.005 μm or more, even more preferably 0.01 μm or more, still more preferably 0.05 μm or more, and even more preferably 0.1 μm or more. When the resin composition of the present embodiment contains two or more types of (D) white colorant, the average primary particle size is preferably such that the weighted average value of the average primary particle sizes of the respective white colorants falls within the above range.

[0049] The content of the (D) white colorant in the resin composition of this embodiment is 0.2 parts by mass or more, preferably 0.5 parts by mass or more, more preferably 1 part by mass or more, more preferably 3 parts by mass or more, even more preferably 5 parts by mass or more, even more preferably 6 parts by mass or more, and even more preferably 8 parts by mass or more, particularly more preferably 10 parts by mass or more, and 20 parts by mass or less, preferably 19 parts by mass or less, more preferably 18 parts by mass or less, even more preferably 17 parts by mass or less, even more preferably 16 parts by mass or less, and may be 14 parts by mass or less, depending on the application. By making it equal to or more than the lower limit, the effect of ensuring hiding power and coloring white tends to be improved. Also, by making it equal to or less than the upper limit, the production stability during blending and kneading tends to be improved. The resin composition of the present embodiment may contain only one type of (D) white colorant having a Mohs hardness of 1.0 to 4.5, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0050] The resin composition of the present embodiment may or may not contain a colorant other than (D) the white colorant having a Mohs hardness of 1.0 to 4.5. The resin composition of the present embodiment preferably does not substantially contain a colorant having a Mohs hardness of more than 4.5. "Substantially free" means that the content of colorants having a Mohs hardness of more than 4.5 is less than 10% by mass of the content of the (D) white colorant having a Mohs hardness of 1.0 to 4.5, preferably less than 5% by mass, more preferably less than 3% by mass, and even more preferably less than 1% by mass.

[0051] <Nucleating agent> The resin composition of the present embodiment may contain a nucleating agent. By containing a nucleating agent, the appearance of the obtained molded article can be improved. The nucleating agent may be an organic nucleating agent or an inorganic nucleating agent, but an inorganic nucleating agent is preferable, and talc is more preferable. The talc used may be surface-treated with at least one compound selected from polyorganohydrogensiloxanes and organopolysiloxanes. In this case, the amount of the siloxane compound attached to the talc is preferably 0.1 to 5 mass% of the talc.

[0052] When the resin composition of the present embodiment contains a nucleating agent, the content thereof is preferably 0.01 parts by mass or more, more preferably 0.05 parts by mass or more, even more preferably 0.1 parts by mass or more, and even more preferably 0.5 parts by mass or more, relative to 100 parts by mass of the polyamide resin (A). The upper limit of the content of the nucleating agent is preferably 5 parts by mass or less, more preferably 3 parts by mass or less, and even more preferably 2 parts by mass or less, relative to 100 parts by mass of the polyamide resin (A). The resin composition of the present embodiment may contain only one type of nucleating agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0053] <Release agent> The resin composition of the present embodiment may contain a release agent. Examples of the release agent include aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, aliphatic hydrocarbon compounds having a number average molecular weight of 200 to 15,000, polysiloxane-based silicone oils, ketone waxes, and fatty acid amides. Of these, aliphatic carboxylic acids, salts of aliphatic carboxylic acids, esters of aliphatic carboxylic acids and alcohols, and fatty acid amides are preferred, and fatty acid amides are more preferred. For details about the release agent, please refer to paragraphs 0055 to 0061 of JP2018-095706A, the contents of which are incorporated herein by reference. When the resin composition of the present embodiment contains a release agent, the content thereof in the resin composition is preferably 0.05 to 3 mass %, more preferably 0.1 to 1 mass %, and even more preferably 0.2 to 0.8 mass %. The resin composition of the present embodiment may contain only one type of release agent, or may contain two or more types. When two or more types are contained, the total amount is preferably in the above range.

[0054] <Other additives> The resin composition of the present embodiment may contain additives other than those described above (other additives). Examples of other additives include heat stabilizers, light stabilizers, antioxidants, ultraviolet inhibitors, alkali, titanium oxide, hydrolysis resistance improvers, matting agents, plasticizers, dispersants, antistatic agents, and antigelling agents. The total amount of the other additives is preferably 20.0 mass % or less of the resin composition, more preferably 10.0 mass % or less, even more preferably 5.0 mass % or less, and even more preferably 1.0 mass % or less. Only one type of the other additives may be used, or two or more types may be used in combination. For details of other additives, refer to paragraphs 0130 to 0155 of Japanese Patent No. 4894982, the contents of which are incorporated herein by reference. In addition, the resin composition of this embodiment can be blended with the additives described in paragraphs 0047 to 0103 of WO 2021 / 241471 without departing from the spirit of the present invention, the contents of which are incorporated herein by reference.

[0055] In the resin composition of this embodiment, the contents of (A) polyamide resin, (B) large diameter glass fiber, (C) phosphorus-based flame retardant, (D) white colorant, and other components blended as necessary are adjusted so that the total of each component is 100 mass%. In this embodiment, the total of (A) polyamide resin, (B) large diameter glass fiber, (C) phosphorus-based flame retardant, (D) white colorant, release agent, and nucleating agent preferably accounts for 90 mass% or more of the resin composition, and more preferably accounts for 95 mass% or more.

[0056] <Characteristics of resin composition> The resin composition of the present embodiment preferably has excellent tracking resistance. Specifically, the resin composition of this embodiment is molded into a flat plate having a thickness of 3 mm or more, and the comparative tracking index (CTI) measured according to IEC 60112 is preferably 710 V or more, more preferably 750 V or more, even more preferably 785 V or more, and even more preferably 800 V or more. The upper limit of the CTI is not particularly set, but the required performance is satisfied even if it is, for example, 2000 V or less.

[0057] The resin composition of the present embodiment preferably has excellent flame retardancy. Specifically, it is preferable that the flame retardancy of a test piece formed to a thickness of 0.4 mm from the resin composition of this embodiment satisfies V-0 in accordance with the UL94 test. Furthermore, the resin composition of this embodiment is molded into a test piece having a thickness of 0.75 mm according to the UL94 test, and the flame retardancy thereof preferably satisfies V-1 or higher, and more preferably satisfies V-0.

[0058] The resin composition of the present embodiment preferably has excellent mechanical strength. The resin composition of the present embodiment preferably has a bending strength of 300 MPa or more, as measured in accordance with ISO 178 by molding the resin composition into an ISO tensile test piece having a thickness of 4 mm, and may further be 305 MPa or more or 310 MPa or more depending on the application, etc. The upper limit of the tensile strength is not particularly set, but for example, 500 MPa or less is practical.

[0059] The resin composition of the present embodiment preferably has a flexural modulus of 17.0 GPa or more, measured in accordance with ISO 178 by molding the resin composition into an ISO tensile test piece having a thickness of 4 mm, and may further be 19.0 GPa or more or 20.0 GPa or more depending on the application, etc. The upper limit of the tensile strength is not particularly set, but for example, 50.0 GPa or less is practical.

[0060] The resin composition of the present embodiment, when molded into an ISO multipurpose test piece (4 mm thick) in accordance with ISO179-1 and 2, has a notched Charpy impact strength of 8 kJ / m under an environment of a temperature of 23° C. and a humidity of 50%. 2 It is preferable that the concentration is 12 kJ / m or more. 2 More preferably, it is 15 kJ / m or more. 2 The upper limit is not particularly specified, but is preferably 40 kJ / m 2 The following is practical.

[0061] The resin composition of the present embodiment preferably has excellent whiteness. Specifically, the resin composition of the present embodiment is molded into a flat plate having a thickness of 3 mm or more, and the whiteness (L * The value is preferably 80 or more, more preferably 85 or more, and even more preferably 87 or more. The upper limit is 100.

[0062] The above tracking resistance, flame retardancy, bending properties, Charpy impact strength and L * The value is measured by the method described in the Examples below.

[0063] <Method of producing resin composition> In the present embodiment, the method for producing the resin composition is not particularly specified, and a wide variety of known methods for producing thermoplastic resin compositions can be used. Specifically, the resin composition can be produced by mixing the components in advance using various mixers such as a tumbler or a Henschel mixer, and then melt-kneading the components using a Banbury mixer, a roll, a Brabender, a single-screw extruder, a twin-screw extruder, a kneader, or the like.

[0064] Also, for example, the resin composition can be produced by not mixing the components in advance, or by mixing only some of the components in advance, feeding the mixture to an extruder using a feeder, and melt-kneading the mixture. Furthermore, for example, some of the components may be mixed in advance, fed to an extruder, and melt-kneaded to obtain a masterbatch composition, which may then be mixed again with the remaining components and melt-kneaded to produce pellets. In addition, it is preferable that the glass fibers are side-fed.

[0065] <Applications of resin compositions and molded products> The molded article of the present embodiment is formed from the resin composition or pellets of the present embodiment. The method for producing the molded article of the present embodiment is not particularly limited. As an example, an injection molded article produced by injection molding is exemplified. For example, the molded product of this embodiment may be produced by melt-kneading the components and then directly molding the components using various molding methods, or by melt-kneading the components and pelletizing them, and then melting them again and molding them using various molding methods.

[0066] The method for molding the molded product is not particularly limited, and any conventionally known molding method can be used, such as injection molding, injection compression molding, extrusion molding, profile extrusion, transfer molding, hollow molding, gas-assisted hollow molding, blow molding, extrusion blow molding, IMC (in-mold coating molding), rotational molding, multi-layer molding, two-color molding, insert molding, sandwich molding, foam molding, and pressure molding.

[0067] The shape of the molded product of the present embodiment is not particularly limited and can be appropriately selected depending on the application and purpose of the molded product. Examples of the shape include plate-like, plate-like, rod-like, sheet-like, film-like, cylindrical, annular, circular, elliptical, gear-like, polygonal, irregularly shaped, hollow, frame-like, box-like, and panel-like shapes.

[0068] The resin composition, pellets, and molded articles of the present embodiment are not particularly defined in terms of their fields of use, and are widely used in transportation machine parts such as automobiles, general machine parts, precision machine parts, electronic and electrical equipment parts, OA equipment parts, building materials and housing-related parts, medical devices, leisure and sports goods, toys, medical products, daily necessities such as food packaging films, and defense and aerospace products. In particular, it is preferably used for battery protection cases, connector protection cases, or circuit relay protection cases.

Examples

[0069] The present invention will be described more specifically with reference to the following examples. The materials, amounts used, ratios, treatment contents, treatment procedures, etc. shown in the following examples can be appropriately changed without departing from the spirit of the present invention. Therefore, the scope of the present invention is not limited to the specific examples shown below. When the measuring instruments used in the examples are difficult to obtain due to being obsolete, etc., measurements can be made using other devices having equivalent performance.

[0070] 1. Raw materials The following raw materials were used.

Table 1

[0071] <Synthesis example of PAMP6> Into a reaction vessel equipped with a stirrer, a partial condenser, a total condenser, a thermometer, a dropping funnel, a nitrogen inlet tube, and a strand die, 7220 g (49.4 mol) of adipic acid (manufactured by Roadia) and 11.66 g of sodium acetate / sodium hypophosphite monohydrate (molar ratio = 1 / 1.5) were charged. After sufficient nitrogen substitution, the system was further heated to 170 °C with stirring under a small amount of nitrogen flow. 6647g of mixed xylylenediamine (34.16mol of metaxylylenediamine, 14.64mol of paraxylylenediamine, manufactured by Mitsubishi Gas Chemical Co., Ltd.) having a molar ratio of metaxylylenediamine and paraxylylenediamine of 70 / 30 was dropped into the melt in the reaction vessel under stirring, and the internal temperature was continuously raised to 260°C over 2.5 hours while discharging the generated condensed water out of the system. After the dropwise addition, the internal temperature was raised, and when it reached 270°C, the pressure in the reaction vessel was reduced, and the internal temperature was further raised to 280°C for 20 minutes to continue the melt polycondensation reaction. Thereafter, the system was pressurized with nitrogen, and the obtained polymer was taken out of the strand die and pelletized to obtain a polyamide resin. The melting point was 256°C.

[0072] 2. Examples 1 to 5 and Comparative Examples 1 to 7 <Compound> The components shown in Table 1 were weighed out as shown in Table 2 or Table 3 (each component is expressed in parts by mass), and the components other than the glass fiber were blended in a tumbler, and the blend was added to the base of a twin-screw extruder (Shibaura Machine Co., Ltd., TEM26SS) and melted. The glass fiber was then side-fed to produce pellets of the resin composition. The temperature of the twin-screw extruder was set to 280°C.

[0073] <Flexural strength and flexural modulus> The thermoplastic resin pellets obtained by the above-mentioned manufacturing method were dried at 80°C for 12 hours, and then injection molded into ISO tensile test specimens (4 mm thick) using an injection molding machine (manufactured by Nissei Plastic Industrial Co., Ltd., "NEX140III") under conditions of a cylinder temperature of 280°C, a mold temperature of 130°C, and a molding cycle of 50 seconds. The flexural strength (unit: MPa) and flexural modulus (unit: GPa) were measured in an environment of 23°C and 50% humidity using the above ISO tensile test pieces (4 mm thick) in accordance with ISO 178. The results are shown in Table 2 or Table 3.

[0074] <Notched Charpy impact strength> In accordance with ISO179-1 and 2, the above ISO tensile test piece (4 mm thick) was used to measure the notched Charpy impact strength (unit: kJ / m) using a 1J hammer at a temperature of 23°C and humidity of 50%. 2 The results are shown in Table 2 or Table 3.

[0075] <Tracking resistance (CTI)> The thermoplastic resin pellets obtained by the above-mentioned manufacturing method were dried at 80°C for 12 hours, and then injection-molded into flat test pieces measuring 100 x 100 mm and 3 mm in thickness using an injection molding machine (Nissei Plastic Industrial Co., Ltd., "NEX140III") under conditions of a cylinder temperature of 280°C, a mold temperature of 130°C, and a molding cycle of 50 seconds. A tracking resistance test was performed using the above-mentioned flat plate specimens of 100 x 100 mm and 3 mm thickness in accordance with IEC 60112, and the tracking resistance voltage was measured. The results are shown in Tables 2 and 3.

[0076] <Flame retardancy (UL94 test)> The polyamide resin pellets obtained by the above-mentioned manufacturing method were dried at 80°C for 12 hours, and then injection molded using an injection molding machine (manufactured by Japan Steel Works, Ltd., "J55AD") to mold UL test specimens with a length of 125 mm, a width of 13 mm, and a thickness of 0.75 mm and 0.4 mm. The cylinder temperature and the mold temperature were 280°C and 130°C, respectively. The UL test specimens obtained by the above method were conditioned in a thermostatic chamber at a temperature of 23°C and a humidity of 50% for 48 hours, and the test was carried out in accordance with UL94. The results are shown in Tables 2 and 3.

[0077] <Color difference> The thermoplastic resin pellets obtained by the above-mentioned manufacturing method were dried at 80°C for 12 hours, and then injection molded into flat test pieces of 100 x 100 mm and 3 mm thick using an injection molding machine (manufactured by Nissei Plastic Industrial Co., Ltd., "NEX140III") under the conditions of a cylinder temperature of 280°C, a mold temperature of 130°C, and a molding cycle of 50 seconds. The L value (brightness) of the above test pieces of 100 x 100 mm and 3 mm thick was measured using a color difference meter (Spectro Color Meter SE6000) (manufactured by Nippon Denshoku Industries Co., Ltd.). The measurement conditions were C light source, viewing angle of 2°, and measurement diameter Φ30 mm reflection. The results are shown in Table 2 or Table 3.

[0078] [Table 2]

[0079] [Table 3]

[0080] As is clear from the above results, the molded article formed from the resin composition of the present embodiment had excellent tracking resistance and flame retardancy. Furthermore, the molded article formed from the resin composition of the present embodiment was excellent in mechanical strength and had a high color difference.

Claims

1. (A) per 100 parts by mass of polyamide resin, (B) 130 μm 2 80 to 230 parts by mass of glass fibers having a cross-sectional area of ​​the above (C) 10 to 50 parts by mass of at least one phosphorus-based flame retardant selected from phosphinates and diphosphinates; (D) A resin composition comprising 0.2 to 20 parts by mass of a white colorant having a Mohs hardness of 1.0 to 4.

5.

2. 2. The resin composition according to claim 1, wherein the polyamide resin (A) is a semi-aromatic polyamide resin and contains a structural unit having a linear aliphatic chain having 4 to 7 carbon atoms.

3. The resin composition according to claim 1 or 2, wherein the glass fiber (B) has a noncircular cross section.

4. The resin composition according to claim 1 or 2, wherein the (B) glass fiber has an aspect ratio, which is a ratio of a long side to a short side of a cross section, of 2 to 7.

5. The resin composition according to claim 1 or 2, wherein the Mohs hardness of the (B) glass fiber is higher than the Mohs hardness of the (D) white colorant.

6. The resin composition according to claim 1 or 2, wherein the (D) white colorant contains zinc sulfide.

7. 3. The resin composition according to claim 1, wherein the polyamide resin (A) contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 70 mol % or more of the diamine-derived structural unit is derived from xylylenediamine.

8. The resin composition according to claim 1 or 2, wherein the resin composition is molded into a plate having a thickness of 3 mm or more and exhibits a tracking resistance voltage of 800 V or more as measured in accordance with IEC 60112.

9. The resin composition according to claim 1 or 2, which is used for a protective case for a battery, a protective case for a connector, or a protective case for a circuit relay.

10. The polyamide resin (A) is a semi-aromatic polyamide resin and contains a structural unit having a linear aliphatic chain having 4 to 7 carbon atoms, The (B) glass fiber has an aspect ratio, which is a ratio of the long side to the short side of a cross section, of 2 to 7; The Mohs hardness of the (B) glass fiber is higher than the Mohs hardness of the (D) white colorant, The (D) white colorant contains zinc sulfide, the polyamide resin (A) contains a diamine-derived structural unit and a dicarboxylic acid-derived structural unit, and 70 mol % or more of the diamine-derived structural unit is derived from xylylenediamine; The resin composition according to claim 1, wherein the resin composition is molded into a plate having a thickness of 3 mm or more and exhibits a tracking resistance voltage of 800 V or more as measured in accordance with IEC 60112.

11. A pellet of the resin composition according to claim 1, 2 or 10.

12. A molded article molded from the resin composition according to claim 1, 2 or 10.

13. A molded article made from the pellets according to claim 11.

Citation Information

Patent Citations

  • Flame-retardant polyamide resin composition and molded article

    JP2008163317A

  • Resin composition and molded article

    JP2020172579A